The Theory and Practice of Online Learning - Terry Anderson (Issues in Distance Education, 2008)
Every chapter in the widely distributed first edition has been updated, and four new chapters on current issues such as connectivism and social software innovations have been added. Essays by practitioners and scholars active in the complex, diverse, and rapidly evolving field of distance education blend scholarship and research; practical attention to the details of teaching and learning; and mindful attention to the economics of the business of education.